2017
DOI: 10.18203/2320-6012.ijrms20171255
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge and healthcare providers’ role in promoting lactation in United Arab Emirates

Abstract: Background: This study was performed to assess mothers’ knowledge and awareness level regarding maternal medication intake during lactation and health care providers’ role in promoting lactation.Methods: This study is a cross-sectional, questionnaire based survey study and a convenient sample of (820) breastfeeding mothers in Ajman and Sharjah, United Arab Emirates (U.A.E.) participated in the study. The results were analyzed using the Statistical Package for the Social Sciences (SPSS) version 20. Descriptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…It was observed that our study result of 17.5% due to new pregnancy was lower than the result interpreted in the study held 3 years ago in UAE, which indicated that this misconception has declined and the mothers are more aware of this matter, and this could be explained due to an improvement, which was observed in terms of knowledge among breastfeeding mothers as well as health-care providers’ role, which was also positively improved, in a recent study held in 2017 in UAE compared to that held in previous years. [ 17 ]…”
Section: R Esults and Discussionmentioning
confidence: 99%
“…It was observed that our study result of 17.5% due to new pregnancy was lower than the result interpreted in the study held 3 years ago in UAE, which indicated that this misconception has declined and the mothers are more aware of this matter, and this could be explained due to an improvement, which was observed in terms of knowledge among breastfeeding mothers as well as health-care providers’ role, which was also positively improved, in a recent study held in 2017 in UAE compared to that held in previous years. [ 17 ]…”
Section: R Esults and Discussionmentioning
confidence: 99%